The Selection of a Suitable Shape for Parallel Tunnels in Case of Changing Surface Conditions - Nguyen Duyen Phong; Tran Tuan Minh; Dang Trung Thanh (Tehnički Vjesnik, 2025)
The process of constructing traffic tunnels through mountains, as well as metro tunnels, often involves using two parallel tunnels to enhance the operating capacity and improve convenience during operation of the tunnels. Currently, analyses of two-tunnel systems frequently assume circular tunnels embedded in an elastic, isotropic, and homogeneous soil mass, with a flat surface. However, in practice tunnels often feature cross-sections of various shapes depending on the intended use and the tunnelling technology employed. The geological conditions are typically complex and do not conform to the assumptions of elasticity or isotropic homogeneity. Tunnel cross-sections can be an arch, horseshoe arch, curved rectangle, ellipse, oval, and other shapes. Additionally, topographical surface conditions often vary and are not flat, as assumed in simplified theoretical problems. Relation to this problem requires in-depth research to ensure effective excavation, protection, and effective use of tunnels. This study investigated the mechanisms of rock mass alteration around tunnels with different cross-sections, considering changes in surface conditions, to determine the most suitable tunnel shapes for various scenarios. The results of the research showed that under both of the flat and changing surface conditions the suitable tunnel shapes are horse-shoe or sub-rectangular. In these cases, the displacement on the boundary of tunnels will be minimized.